Adolescents’ Sexual Wellbeing in Southwestern Uganda: A Cross-Sectional Assessment of Body Image, Self-Esteem and Gender Equitable Norms - Kemigisha, Elizabeth; Nyakato, Viola N.; Bruce, Katharine; Ruzaaza, Gad Ndaruhutse; Mlahagwa, Wendo; Ninsiima, Anna B.; Coene, Gily; Leye, Els; Michielsen, Kristien (MDPI, 2017)
Measures of sexual wellbeing and positive aspects of sexuality in the World Health Organization definition for sexual health are rarely studied and remain poorly understood, especially among adolescents in Sub-Saharan Africa. The objective of this study was to assess sexual wellbeing in its broad sense—i.e., body image, self-esteem, and gender equitable norms—and associated factors in young adolescents in Uganda. A cross-sectional survey of adolescents ages 10–14 years in schools was carried out between June and July 2016. Among 1096 adolescents analyzed, the median age was 12 (Inter-Quartile Range (IQR): 11, 13) and 58% were female. Self-esteem and body image scores were high with median 24 (IQR: 22, 26, possible range: 7–28) and median 22 (IQR: 19, 24, possible range: 5–25) respectively. Gender equitable norms mean score was 28.1 (SD 5.2: possible range 11–44). We noted high scores for self-esteem and body image but moderate scores on gender equitable norms. Girls had higher scores compared to boys for all outcomes. A higher age and being sexually active were associated with lower scores on gender equitable norms. Gender equitable norms scores decreased with increasing age of adolescents. Comprehensive and timely sexuality education programs focusing on gender differences and norms are recommended
Adolescents’ SexualWellbeing in Southwestern Uganda.
Keywords: self-esteem; gender norms; body image; young adolescents; Uganda; sexuality; sexual health